Analisa Perbandingan Proses Pembuatan Laporan Keuangan Antara Manual dan Terkomputerisasi - Rachmawati, Susan (www.bsi.ac.id, 2015)
Technological developments are encouraging everyone to work more effectively and efficiently as well as in generating financial reports. As we know together with the financial statements of one of the tools used by the company in assessing the success or decline of financial activities performed during a certain period and will result in a fatal impact given wrong/incorrect. By using the calculation manually accounting process that must be traversed into very long in accordance with the accounting cycle i.e. from transaction documents that exist to make a journal and then the book of the balance of the existing big dibuku the final produced a balance sheet balances continued by journal of adjustments and balance columns of newly acquired financial reports for it required a system of accounting information in this regard zahir to shorten the process to be undertaken in producing the financial statements i.e. insert existing transactions in the journal module available by zahir and the system will process the direct dperoleh of the results (financial report) as desired. The methods used in the writing of this literature is the study and conclusions. Whereas the results obtained was using accounting information systems (zahir) can shorten the time of the making of the financial statements. Because the process is a system that is far from tired properties then the accuracy of the resulting financial statement results be better compared to the accounting manual and for system operators need not have to be skilled in the accounting cycle but by understanding each module provided by the system then the desired financial reports can be generated. Keywords: accounting, manual, sia